A Drowned Diver – Four Expert Witness Opinions – Who is Right? - Lalić, Hrvoje (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The paper describes the case of a drowned diver in the Adriatic Sea near Pula, Croatia. CASE PRESENTATION: The deceased diver had not been trained at any Health and Safety at Work programs nor had he been examined by the occupational medicine (OM) specialist. The pathologist in Pula concluded that this accident was caused by drowning and that diver’s blood was saturated with 38% carboxyhemoglobin (COHb). The second pathologist in Zagreb concluded that the diver drowned due to atherosclerosis sickness but that COHb was not present in his blood. The third expert witness from Forensics in Rijeka evaluated that the diver died due to increased exertion while diving, due to atherosclerosis and weakened heart. The fourth, the OM specialist expert witness from Rijeka, explained that the diver was a healthy athlete who died due to faulty diving equipment. CONCLUSION: Persons who work under the special working conditions should be examined at an Occupational medicine department as well as trained for work in a safe way. Periodical examinations and permanent training courses should be provided. That way the risk of fatal accidents would be reduced to a minimum.